A hiatus in the tropopause layer change. (1st June 2017) - Xian, Tao; Fu, Yunfei
ABSTRACT: Despite continually increasing concentrations of greenhouse gas, there has been a hiatus in rising global temperatures during the 21st century. In this study, changes in the tropopause layer (TL) thickness are studied during the pre‐hiatus and the hiatus periods, based on radiosonde data from the Integrated Global Radiosonde Archive. Statistically significant thickening occurs in the Northern (Southern) Hemisphere extratropics, at 35 ± 15.6 (59.0 ± 27.6) m decade −1, and the Northern (Southern) Hemisphere high latitudes, at 104.8 ± 21.7 (132.6 ± 97.4) m decade −1, but not in the tropics during the pre‐hiatus period (1960–1997). For the hiatus period (2002–2013), significant thickening of the TL occurs only in the Southern Hemisphere extratropics (133 ± 98 m decade −1 ). Moreover, this study captures distinct regional characteristics in the hiatus of the TL thickening, including thinning over Alaska, Hawaii, the Western Plateau of North America, and Northern Australia. Abstract : Statistically significant thickening of the tropopause layer occurs in the Northern (Southern) Hemisphere extratropics, at 35 ± 15.6 (59.0 ± 27.6) m decade −1, and the Northern (Southern) Hemisphere high latitudes, at 104.8 ± 21.7 (132.6 ± 97.4) m decade −1 during the pre‐hiatus period (1960–1997). For the hiatus period (2002‐2013), significant thickening of the tropopause layer only occurs in the Southern Hemisphere extratropics (133 ± 98 m decade −1 ). The distinct regional characteristics in the hiatus of the tropopause layer thickening was captured, including thinning over Alaska, Hawaii, the Western Plateau of North America, and Northern Australia.